Synthesis and gas separation application of radiation grafting mixed matrix membrane

By induced small molecule polymerization by using electron radiation in glassy polymer films, the phase interface defects and ion agglomeration problems existing in existing hybrid matrix membranes in gas separation applications are solved, and a high-performance gas separation membrane is achieved.

CN119391044APending Publication Date: 2025-02-07HUBEI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411764592.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-08-28
Filing Date
2024-12-04
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing glassy polymer mixed matrix membranes have problems such as phase interface defects and ion agglomeration in gas separation applications, which affect their gas separation performance.

Method used

By designing a new radiation-grafted hybrid matrix membrane, electron radiation is used to induce polymerization of small molecules in the sheet layer of glassy film, small molecules are polymerized in situ to achieve deposition in the membrane, changing the pore structure of the membrane material, thereby improving gas separation performance.

Benefits of technology

The obtained mixed matrix membrane has excellent performance and defect-free polymer distribution, and has good CO2/CH4, CO2/N2, and O2/N2 selectivity, meeting the needs of industrial gas separation applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391044A_ABST
    Figure CN119391044A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing a novel mixed matrix membrane by irradiating a micromolecule and self-polymerizing a microporous polymer membrane. According to the method, different types of olefin small molecules and different types of polymer membranes are taken as substrates, and due to a special molecular structure, high-yield in-situ polymerization of small molecule compounds is induced by radiation, and the small molecule compounds are deposited in polymer membrane chains in situ. The pore channel structure of the self-polymerized microporous polymer is adjusted by utilizing the content of the newly obtained polymer, and the pore channel beneficial to gas screening is obtained. The method has the advantages that operation is simple, raw materials are cheap and easy to obtain, and the prepared mixed matrix membrane is free of defects, excellent in performance and the like, and has good industrial application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a synthesis method for preparing a mixed matrix membrane by radiation grafting small molecules and polymer membranes and its application in the field of gas separation. Technical Background

[0002] Gas separation membrane technology is an emerging "green technology" that has been widely concerned for its advantages such as low energy consumption, simple equipment, convenient and flexible operation, etc. However, the gas separation performance of a single polymer membrane material is not enough to meet industrial requirements, so more and more researchers have begun to pay attention to new polymer membrane materials with high separation performance.

[0003] Mixed matrix membrane carbon is a new type of membrane separation material. Introducing porous inorganic materials with good gas separation performance into polymers to prepare mixed matrix membranes is one of the effective means to improve the gas separation performance of polymer membranes. For example, the introduction of molecular sieves, activated carbon, carbon nanotubes, metal organic framework materials, etc. improves the gas separation performance of membrane materials. However, the glassy polymers that are currently used more often have rigid chain structure, and the prepared mixed matrix membranes are prone to defects such as phase interface defects and ion agglomeration, which affect the gas separation performance of membrane materials. For this reason, it is necessary to develop new synthetic methods for mixed matrix membranes to solve the problems faced by existing mixed matrix membranes. Therefore, it is of great significance to strengthen the research on membrane preparation and promote the preparation of membranes by studying the gas separation process from a mechanistic perspective.

[0004] In order to meet the requirements of industrial practical applications, a carbon molecular sieve membrane with both high selectivity and high permeability is synthesized. The present invention designs a new type of radiation grafted mixed matrix membrane, uses electron radiation to induce small molecules to polymerize in the glassy membrane layer, and realizes in situ small molecule polymerization and deposition in the membrane to change the pore structure of the glassy membrane material and thus change its gas separation performance. The present invention is intended to maintain the structural integrity of the original membrane material, seamlessly introduce polymers into the membrane material to improve the gas separation performance of the original membrane material, and is expected to meet the needs of industrial development. Summary of the invention

[0005] The purpose of the present invention is to synthesize a variety of self-polymerizing microporous polyimide polymers and a variety of small molecule compounds containing double bonds, use radiation to induce the polymerization of small molecules to form polymers, in situ deposit them in the self-polymerizing microporous polymer membrane chain, obtain a new type of mixed matrix membrane, and apply it to gas separation membranes to study the gas separation performance of the mixed matrix membrane.

[0006] The self-polymerized microporous polyimide polymer of the present invention contains a small molecule compound with double bonds. Due to its special molecular structure, it can be irradiated to induce high-yield in-situ polymerization of the small molecule compound and deposited in-situ in the polymer film chain. The pore structure of the self-polymerized microporous polymer is adjusted by utilizing the content of the newly obtained polymer to obtain pores that can be used for gas screening.

[0007] To achieve the above object, the technical solution adopted by the present invention is: Preparation of diamine monomers required for the synthesis of polyimide diamine, the structural formula of which is as follows: ; Self-polymerizing microporous polyimide, the general structure is as follows: ; The polyimide is a homopolymer or a random copolymer, wherein n represents the degree of polymerization, n is a positive integer of 10-200, and the weight average molecular weight is between 10000-600000.

[0008] R 1 Representative is one or more of the above diamines: Where R 1 The structural characteristics are: a series of self-polymerized microporous polymers have the following structures, these structures are polymers with a ladder-like structure, and the ladder-like structure can increase the distance between polymer chains, reduce polymer stacking, and provide a large number of micropores.

[0009] R 2 Represents one or more of the following structures: .

[0010] The synthesis of polyimide polymerization of the present invention comprises the following steps: Under nitrogen atmosphere, add organic solvent to a three-necked round-bottomed bottle containing diamine monomer. After it is completely dissolved, add R 2 One or two dianhydrides of the structure are added, stirred for 24 hours after being completely dissolved, and then acetic anhydride and 2-methylpyridine are added, and stirring is continued for 24 hours. After the viscous reaction liquid is cooled to room temperature, it is precipitated in a methanol solution to obtain a fibrous polymer. After washing 4 times, the obtained polymer is vacuum dried at 100°C for 12 hours. Wherein: the concentration of the diamine monomer and the dianhydride of the R2 structure in the reaction system in the organic solvent is 15-20wt%, the diamine monomer and R 2 The molar amount of dianhydride of the same structure is the same, the molar amount of acetic anhydride is 10 times that of the monomer, and the molar amount of 3-methylpyridine is 2 times that of the monomer.

[0011] The synthesis method of the membrane material of the present invention (taking GMA as an example) comprises the following steps: The prepared polymer is dissolved in a polar organic solvent to obtain a 7-10% casting solution, stirred at room temperature for 12-24 hours, filtered, poured onto a clean horizontal glass plate, and vacuum dried at 60-100°C for 6-20 hours to obtain a self-microporous polymer membrane with a thickness of 40-60 um. The synthesized self-polymerized microporous polymer membrane is soaked in a 5%-30% GMA methanol solution for 12 hours, then sealed in a plastic film, and irradiated for 5-30 minutes at 20-200 kGy under an electron accelerator. After the irradiation is completed. The plastic film is placed at room temperature to react for 4 hours. After GMA is completely polymerized, the self-polymerized microporous polymer membrane is taken out and ultrasonically washed in methanol to clean all the poly GMA attached to the surface, 80-100 o C drying, weighing and calculating the grafting rate of PGMA.

[0012] The beneficial results of the present invention are: (1) This invention synthesized a new type of mixed matrix membrane for the first time ( Figure 1 ); (2) In different small molecule solutions, radiation induces in situ cross-linking polymerization of small molecules, and in situ deposition inside the self-polymerized microporous membrane. The obtained mixed matrix membrane has no defects, and the polymer distribution in the membrane with better performance is relatively uniform (taking the cross-sectional distribution diagram of TB / PGMA as an example, Figure 2 ); (3) The resulting mixed matrix membrane has good CO 2 Adsorption and suitable pore size distribution (taking PIM-1 / PGMA as an example, Figure 3 ); (4) A new mixed matrix membrane was prepared by in situ radiation deposition. The obtained membrane has good CO 2 / CH 4 , CO 2 / N 2 , and O 2 / N 2 Selectivity, can meet the practical application of gas separation ( Figure 4 ). BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 It is a schematic diagram of the formation process of the mixed matrix membrane of the present invention.

[0014] Figure 2 This is a schematic diagram of the SEM cross-sectional distribution of PGMA in the TB film, where (a) is 7.0% pGMA, (b) is 13.9% pGMA, (c) is 25.1% pGMA, and (d) is 40.0% pGMA.

[0015] Figure 3PIM-1 / PGMA mixed matrix membrane, (a) CO2 adsorption diagram, (b) pore size distribution diagram.

[0016] Figure 4 The performance of PIM-1 / PGMA mixed matrix membrane: (a) is the flux diagram of CH4, (b) is the flux diagram of CO2, (c) is the flux of O2 and N2, (d) is the selectivity of CO2 / CH4, (e) is the selectivity of CO2 / N2, and (f) is the selectivity of O2 / N2. DETAILED DESCRIPTION

[0017] The following embodiments are intended to further illustrate the present invention rather than to limit the scope of the present invention. Example

[0018] The prepared PIM-1 polymer was dissolved in chloroform organic solvent to obtain a 7% casting solution, stirred at room temperature for 12 hours, filtered, and poured onto a clean horizontal glass plate, dried at room temperature for 20 hours to obtain a PIM-1 membrane with a thickness of 40-60 um. The synthesized PIM-1 membrane was soaked in a 5% GMA methanol solution for 12 hours, then sealed in a plastic film, and irradiated for 15 minutes at 20 kGy under an electron accelerator. After the irradiation, the plastic film was placed at room temperature for reaction for 4 hours. After GMA was completely polymerized, the self-polymerized microporous polymer membrane was taken out and ultrasonically washed in methanol to clean all the poly GMA attached to the surface, 80-100 o C and dried to obtain a PIM-1 / PGMA-6.3% mixed matrix membrane.

[0019] At 35°C, the gas separation membrane has a high 2 and CO 2 The permeability coefficients are 612 Barrer and 4365 Barrer, respectively. 2 / N 2 and CO 2 / CH 4 The permselectivities are 3.4 and 14.6. Example

[0020] The prepared PIM-1 polymer was dissolved in chloroform organic solvent to obtain 8% casting solution, stirred at room temperature for 16 hours, filtered, poured onto a clean horizontal glass plate, and dried at room temperature for 20 hours to obtain a PIM-1 membrane with a thickness of 40-60 um. The synthesized PIM-1 membrane was soaked in 10% GMA methanol solution for 12 hours, then sealed in a plastic film, and irradiated for 15 minutes at 40 kGy under an electron accelerator. After the irradiation, the plastic film was placed at room temperature for reaction for 4 hours. After GMA was completely polymerized, the self-polymerized microporous polymer membrane was taken out and ultrasonically washed in methanol to clean all the poly GMA attached to the surface. o C and dried to obtain a PIM-1 / PGMA-15.4% mixed matrix membrane.

[0021] At 35°C, the gas separation membrane has a high 2 and CO 2 The permeability coefficients are 465 Barrer and 2744 Barrer, respectively. 2 / N 2 and CO 2 / CH 4 The permselectivity is 5.0 and 36.1, H 2 and C 2 H 6 The permeability coefficients are 2280 Barrer and 109 Barrer, respectively. 2 H 4 / C 2 H 6 and H 2 / CH 4 The permselectivities are 3.3 and 30.0. Example

[0022] The prepared PIM-1 polymer was dissolved in chloroform organic solvent to obtain a 9% casting solution, stirred at room temperature for 20 hours, filtered, and poured onto a clean horizontal glass plate, dried at room temperature for 20 hours to obtain a PIM-1 membrane with a thickness of 40-60 um. The synthesized PIM-1 membrane was soaked in a 20% PDS methanol solution for 12 hours, then sealed in a plastic film, and irradiated for 15 minutes at 100 kGy under an electron accelerator. After the irradiation, the plastic film was placed at room temperature for 4 hours. After the PDS was completely polymerized, the self-polymerized microporous polymer membrane was taken out, ultrasonically washed in methanol, and all the poly PDS attached to the surface was washed clean, and dried at 90 oC to obtain a PIM-1 / PPDS-23.4% mixed matrix membrane.

[0023] At 35°C, the permeability coefficients of the gas separation membrane to O2 and CO2 are 257 Barrer and 1724 Barrer, respectively, and the permeability selectivities of O2 / N2 and CO2 / CH4 are 6.6 and 52.1. Example

[0024] The prepared PIM-1 polymer was dissolved in chloroform organic solvent to obtain a 10% casting solution, stirred at room temperature for 24 hours, filtered, poured onto a clean horizontal glass plate, dried at room temperature for 20 hours, and obtained a PIM-1 membrane with a thickness of 40-60 um. The synthesized PIM-1 membrane was soaked in a 15% PDS methanol solution for 12 hours, then sealed in a plastic film, and irradiated for 15 minutes at 200 kGy under an electron accelerator. After the irradiation was completed, the plastic film was placed at room temperature for reaction for 4 hours. After the PDS was completely polymerized, the self-polymerized microporous polymer membrane was taken out, ultrasonically washed in methanol, and all the poly GMA attached to the surface was washed clean, and dried at 100 oC to obtain a PIM-1 / PPDS-30.3% mixed matrix membrane.

[0025] At 35°C, the permeability coefficients of the gas separation membrane for O2 and CO2 are 234 Barrer and 1688 Barrer respectively, the permeability selectivities of O2 / N2 and CO2 / CH4 are 5.5 and 42.4, the permeability coefficients of H2 and C2H6 are 1907 Barrer and 35 Barrer respectively, the permeability selectivities of C2H4 / C2H6 and H2 / CH4 are 3.3 and 79.3. Example

[0026] The prepared 6FDA-J polymer was dissolved in chloroform organic solvent to obtain a 7% casting solution, which was stirred at room temperature for 12 hours. After filtering, the casting solution was poured onto a clean horizontal glass plate and dried at room temperature for 20 hours to obtain a 6FDA-J membrane with a thickness of 40-60 um. The synthesized 6FDA-J membrane was soaked in a 10% GMA methanol solution for 12 hours, then sealed in a plastic film, and irradiated for 15 minutes at 120 kGy under an electron accelerator. After the irradiation was completed, the plastic film was placed at room temperature for reaction for 4 hours. After GMA was completely polymerized, the self-polymerized microporous polymer membrane was taken out and ultrasonically washed in methanol to clean all the polyGMA attached to the surface. 80 o C and dried to obtain a 6FDA-J / PGMA-15.1% mixed matrix membrane.

[0027] At 35°C, the gas separation membrane has a high 2 and CO 2 The permeability coefficients are 57 Barrer and 319 Barrer, respectively. 2 / N 2and CO 2 / CH 4 The permeation selectivity is 4.9 and 42.2, H 2 and C 2 H 6 The permeability coefficients are 675 Barrer and 0.32 Barrer, respectively. 2 H 4 / C 2 H 6 and H 2 / CH 4 The permselectivities are 6.3 and 90.0. Example

[0028] The prepared 6FDA-J polymer was dissolved in chloroform organic solvent to obtain 8% casting solution, stirred at room temperature for 16 hours, filtered, poured onto a clean horizontal glass plate, and dried at room temperature for 20 hours to obtain a 6FDA-J membrane with a thickness of 40-60 um. The synthesized 6FDA-J membrane was soaked in 20% GMA methanol solution for 12 hours, then sealed in a plastic film, and irradiated for 15 minutes at 100 kGy under an electron accelerator. After the irradiation, the plastic film was placed at room temperature for reaction for 4 hours. After GMA was completely polymerized, the self-polymerized microporous polymer membrane was taken out and ultrasonically washed in methanol to clean all the poly GMA attached to the surface. o C and dried to obtain a 6FDA-J / PGMA-21.7% mixed matrix membrane.

[0029] At 35°C, the gas separation membrane has a high 2 and CO 2 The permeability coefficients are 16.1 Barrer and 109 Barrer, respectively. 2 / N 2 and CO 2 / CH 4 The permeation selectivity is 5.2 and 64.1, H 2 and C 2 H 6 The permeability coefficients are 394 Barrer and 0.88 Barrer, respectively. 2 H 4 / C 2 H 6 and H 2 / CH 4 The permselectivities are 6.6 and 232.0. Example

[0030] The prepared 6FDA-J polymer was dissolved in chloroform organic solvent to obtain a 9% casting solution, stirred at room temperature for 20 hours, filtered, and poured onto a clean horizontal glass plate, dried at room temperature for 20 hours to obtain a 6FDA-J membrane with a thickness of 40-60 um. The synthesized 6FDA-J membrane was soaked in a 10% PA methanol solution for 12 hours, then sealed in a plastic film, and irradiated for 15 minutes at 150 kGy under an electron accelerator. After the irradiation, the plastic film was placed at room temperature for reaction for 4 hours. After PA was completely polymerized, the self-polymerized microporous polymer membrane was taken out, ultrasonically washed in methanol, and all the poly-GMA attached to the surface was washed clean, and dried at 90 oC to obtain a 6FDA-J / PA-32.7% mixed matrix membrane.

[0031] At 35°C, the permeability coefficients of the gas separation membrane for O2 and CO2 are 5.9 Barrer and 28 Barrer respectively, the permeability selectivities of O2 / N2 and CO2 / CH4 are 5.4 and 40.6, the permeability coefficients of H2 and C2H6 are 79 Barrer and 0.32 Barrer respectively, and the permeability selectivities of C2H4 / C2H6 and H2 / CH4 are 6.3 and 114.5. Example

[0032] The prepared 6FDA-J polymer was dissolved in chloroform organic solvent to obtain a 10% casting solution, stirred at room temperature for 24 hours, filtered, poured onto a clean horizontal glass plate, and dried at room temperature for 20 hours to obtain a 6FDA-J membrane with a thickness of 40-60 um. The synthesized 6FDA-J membrane was soaked in a 10% SE methanol solution for 12 hours, then sealed in a plastic film, and irradiated for 15 minutes at 200 kGy under an electron accelerator. After the irradiation, the plastic film was placed at room temperature for reaction for 4 hours. After SE was completely polymerized, the self-polymerized microporous polymer membrane was taken out, ultrasonically washed in methanol, and all the polySE attached to the surface was washed clean, and dried at 80-100 oC to obtain a 6FDA-J / PSE-30.5% mixed matrix membrane.

[0033] At 35°C, the permeability coefficients of the gas separation membrane for O2 and CO2 are 9.2 Barrer and 49.2 Barrer respectively, the permeability selectivities of O2 / N2 and CO2 / CH4 are 5.4 and 57.261.5, the permeability coefficients of H2 and C2H6 are 134 Barrer and 1.23 Barrer respectively, the permeability selectivities of C2H4 / C2H6 and H2 / CH4 are 5.5 and 167.5. Example

[0034] The prepared TB polymer was dissolved in chloroform organic solvent to obtain a 7% casting solution, stirred at room temperature for 12 hours, filtered, and poured onto a clean horizontal glass plate, dried at room temperature for 20 hours to obtain a TB film with a thickness of 40-60 um. The synthesized TB film was soaked in a 10% GMA methanol solution for 12 hours, then sealed in a plastic film, and irradiated for 15 minutes at 80 kGy under an electron accelerator. After the irradiation, the plastic film was placed at room temperature to react for 4 hours. After GMA was completely polymerized, the self-polymerized microporous polymer film was taken out and ultrasonically washed in methanol to clean all the poly GMA attached to the surface, 80-100 o C drying to obtain a TB / PGMA-13.9% mixed matrix membrane.

[0035] At 35°C, the gas separation membrane has a high 2 and CO 2 The permeability coefficients are 17.6 Barrer and 79 Barrer, respectively. 2 / N 2 and CO 2 / CH 4 The perm selectivity is 4.9 and 30.3, H 2 and C 2 H 6 The permeability coefficients are 222 Barrer and 0.45 Barrer, respectively. 2 H 4 / C 2 H 6 and H 2 / CH 4 The permeation selectivities are 7.3 and 85.8. Example

[0036] The prepared TB polymer was dissolved in chloroform organic solvent to obtain 8% casting solution, stirred at room temperature for 16 hours, filtered, poured onto a clean horizontal glass plate, and dried at room temperature for 20 hours to obtain a TB film with a thickness of 40-60 um. The synthesized TB film was soaked in 20% GMA methanol solution for 12 hours, then sealed in a plastic film, and irradiated for 15 minutes under an electron accelerator at 150 kGy. After the irradiation, the plastic film was placed at room temperature for reaction for 4 hours. After GMA was completely polymerized, the self-polymerized microporous polymer film was taken out and ultrasonically washed in methanol to clean all the poly GMA attached to the surface. o C and dried to obtain a TB / PGMA-25.1% mixed matrix membrane.

[0037] At 35°C, the gas separation membrane has a high 2 and CO 2The permeability coefficients are 7.6 Barrer and 39 Barrer, respectively. 2 / N 2 and CO 2 / CH 4 The permselectivity is 5.8 and 47.0, H 2 and C 2 H 6 The permeability coefficients are 107 Barrer and 0.32 Barrer, respectively. 2 H 4 / C 2 H 6 and H 2 / CH 4 The permselectivities are 6.3 and 128.9. Example

[0038] The prepared TB polymer was dissolved in chloroform organic solvent to obtain a 9% casting solution, stirred at room temperature for 20 hours, filtered, and poured onto a clean horizontal glass plate, dried at room temperature for 20 hours to obtain a TB film with a thickness of 40-60 um. The synthesized TB film was soaked in a 10% PA methanol solution for 12 hours, then sealed in a plastic film, and irradiated for 15 minutes at 100 kGy under an electron accelerator. After the irradiation, the plastic film was placed at room temperature for reaction for 4 hours. After the PA was completely polymerized, the self-polymerized microporous polymer film was taken out and ultrasonically washed in methanol to clean all the polyPA attached to the surface. 80-100 o C drying to obtain TB / PPA-19.9% ​​mixed matrix membrane.

[0039] At 35°C, the gas separation membrane has a high 2 and CO 2 The permeability coefficients are 8.4 Barrer and 42 Barrer, respectively. 2 / N 2 and CO 2 / CH 4 The permselectivity is 5.3 and 42.1, H 2 and C 2 H 6 The permeability coefficients are 97 Barrer and 0.35 Barrer, respectively. 2 H 4 / C 2 H 6 and H 2 / CH 4 The permeation selectivities are 5.8 and 97.9. Example

[0040] The prepared TB polymer was dissolved in chloroform organic solvent to obtain a 10% casting solution, stirred at room temperature for 24 hours, filtered, and poured onto a clean horizontal glass plate, dried at room temperature for 20 hours to obtain a TB film with a thickness of 40-60um. The synthesized TB film was soaked in a 10% pMSE methanol solution for 12 hours, then sealed in a plastic film, and irradiated for 15 minutes at 200 kGy under an electron accelerator. After the irradiation, the plastic film was placed at room temperature for reaction for 4 hours. After the pMSE was completely polymerized, the self-polymerized microporous polymer film was taken out and ultrasonically washed in methanol to clean all the poly GMA attached to the surface, 80-100 o C drying to obtain TB / PpMSE-22.7% mixed matrix membrane.

[0041] At 35°C, the gas separation membrane has a high 2 and CO 2 The permeability coefficients are 9.8 Barrer and 33 Barrer, respectively. 2 / N 2 and CO 2 / CH 4 The permselectivity is 5.0 and 34.9, H 2 and C 2 H 6 The permeability coefficients are 89 Barrer and 0.44 Barrer, respectively. 2 H 4 / C 2 H 6 and H 2 / CH 4 The permeation selectivities are 5.6 and 93.6. Example

[0042] The prepared 6FDA-D polymer was dissolved in chloroform organic solvent to obtain a casting solution of 7, stirred at room temperature for 12-24 hours, filtered, poured onto a clean horizontal glass plate, and dried at room temperature for 20 hours to obtain a 6FDA-D film with a thickness of 40-60 um. The synthesized 6FDA-D film was soaked in a 10% GMA methanol solution for 12 hours, then sealed in a plastic film, and irradiated for 15 minutes at 100 kGy under an electron accelerator. After the irradiation, the plastic film was placed at room temperature for reaction for 4 hours. After GMA was completely polymerized, the self-polymerized microporous polymer film was taken out and ultrasonically washed in methanol to clean all the poly GMA attached to the surface, 80-100 o C and dried to obtain a 6FDA-D / PGMA-17.7% mixed matrix membrane.

[0043] At 35°C, the gas separation membrane has a high 2 and CO2 The permeability coefficients are 5.1 Barrer and 69 Barrer, respectively. 2 / N 2 and CO 2 / CH 4 The permselectivity is 5.8 and 56.2, H 2 and C 2 H 6 The permeability coefficients are 104 Barrer and 0.33 Barrer, respectively. 2 H 4 / C 2 H 6 and H 2 / CH 4 The permselectivities are 4.6 and 85.2. Example

[0044] The prepared 6FDA-D polymer was dissolved in chloroform organic solvent to obtain a 10% casting solution, stirred at room temperature for 12-24 hours, filtered, and poured onto a clean horizontal glass plate, dried at room temperature for 20 hours to obtain a 6FDA-D membrane with a thickness of 40-60 um. The synthesized 6FDA-D membrane was soaked in a 10% PDS methanol solution for 12 hours, then sealed in a plastic film, and irradiated for 15 minutes at 100 kGy under an electron accelerator. After the irradiation, the plastic film was placed at room temperature for reaction for 4 hours. After the PDS was completely polymerized, the self-polymerized microporous polymer membrane was taken out and ultrasonically washed in methanol to clean all the poly PDS attached to the surface, 80-100 o C and dried to obtain a mixed matrix membrane with 6FDA-D / P PDS -22.7%.

[0045] At 35°C, the gas separation membrane has a high 2 and CO 2 The permeability coefficients are 6.6 Barrer and 88 Barrer, respectively. 2 / N 2 and CO 2 / CH 4 The permeation selectivity is 5.4 and 46.5, H 2 and C 2 H 6 The permeability coefficients are 144 Barrer and 0.53 Barrer, respectively. 2 H 4 / C 2 H 6 and H 2 / CH 4 The permselectivities are 6.5 and 166.7.

[0046] Gas separation test: The obtained carbon membrane was fixed on the test cell and its separation performance was tested by constant volume and pressure method. The test area was about 0.6 cm 2 , the upstream pressure was controlled at about 0.6MPa, the test temperature was 35°C, and the downstream pressure was monitored. The following table shows the gas separation test results of each film formed and tested Table 1: Gas separation flux and selectivity of polymers .

Claims

1. A method for preparing a radiation grafted mixed matrix membrane and its application, comprising the following steps: Different types of self-polymerizing microporous polymers are utilized: ; The self-polymerized microporous polymer is a homopolymer or a random copolymer, wherein n represents the degree of polymerization, n is a positive integer of 10-200, and the weight average molecular weight is between 10000-600000; R1 represents one or more of the following structures: ; R2 represents one or more of the following structures: ; The self-polymerized microporous polymer is prepared into a film with a thickness of 50-60 um, and the film is immersed in a solution of small molecules of different concentrations. Then, the solution containing the film is irradiated by electron beam irradiation technology, and irradiation cross-linking polymerization is carried out at an irradiation dose of 20KGy-200KGy. After a period of time, the irradiation is stopped, and the reaction is continued in a water bath at different temperatures for 2-6 hours. The small molecules and polymers on the surface of the film are ultrasonically cleaned, and the mixed matrix membrane is obtained by drying.

2. The method for preparing a radiation grafted mixed matrix membrane according to claim 1, characterized in that: In the step (1), the small molecule is one or more of glycidyl methacrylate (GMA), styrene (SE), diphenylethylene (PDS), p-methylstyrene (p-MSE) or acrylic acid (PA).

3. The method for preparing a radiation grafted mixed matrix membrane as claimed in claim 1, wherein the solvent used for dissolving the small molecules in the solution can be one or more of DMF, DMAC, NMP, HCCl3, CH2Cl2, acetone, methanol and ethanol.

4. The use of the radiation grafted mixed matrix membrane in gas separation as claimed in claim 1, comprising the following steps: (1) Rapidly take out the prepared carbon membrane and install it in a gas separation device to test the gas separation performance of the membrane; (2) The device must be vacuumed for more than 12 hours; (3) Test the separation of gases such as C2H4, C2H6, C3H6, C3H8, CH4, N2, O2, H2, He, CO2, etc.

5. The gas separation performance test of the radiation grafted mixed matrix membrane according to claim 4, characterized in that The separation performance was tested by constant volume and pressure variation method, and the test area was about 0.06-0.03cm 2 The upstream pressure is controlled at about 0.6-1.5MPa, and the test temperature is 35 o C, monitor downstream pressure.